2012
DOI: 10.1111/j.1439-0523.2012.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability, genetic diversity and heterosis in relation to F1 performance of tropically adapted shrunken (sh2) sweet corn lines

Abstract: With 6 tables Abstract The objectives of this study were to evaluate the importance of heterosis for agronomic and quality traits in shrunken (sh2) sweet corn, assess the usefulness of combining ability to predict the value of parents and their crosses for further genetic improvement and examine whether genetic divergence can predict heterosis or F1 performance. Ten genetically diverse shrunken (sh2) sweet corn inbred lines were used to generate 45 F1s. F1s and parents were evaluated for agronomic and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
5
10
0
1
Order By: Relevance
“…The highest positive heterosis percentages were exhibited by cross P1×P4 (17.21 %) over mid parents and P4×P6 (8.45%) over better parent. These results are in confidence with those of Abdel- Moneam et al (2009), Patel et al (2009), Amiruzzaman et al (2010, Amanullah et al (2011), Solomon et al (2012, Attia et al (2013) and Abdel- Moneam et al (2014).…”
Section: -Estimates Of Heterosissupporting
confidence: 88%
See 1 more Smart Citation
“…The highest positive heterosis percentages were exhibited by cross P1×P4 (17.21 %) over mid parents and P4×P6 (8.45%) over better parent. These results are in confidence with those of Abdel- Moneam et al (2009), Patel et al (2009), Amiruzzaman et al (2010, Amanullah et al (2011), Solomon et al (2012, Attia et al (2013) and Abdel- Moneam et al (2014).…”
Section: -Estimates Of Heterosissupporting
confidence: 88%
“…Haddadi et al (2012) reported that combined analysis of variance showed significant mean squares of general combining ability (GCA) and specific combing ability (SCA) indicating the importance of both additive and non-additive genetic effects for these traits. Solomon et al (2012) found that heterosis was more important for yield-related traits than it was for ear aspects. Heterosis for most traits was mostly dependent on dominance genetic effects of parental lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, phenotypic traits are influenced by environmental factors. In contrast, molecular markers are not and can be used to detect genetic diversity among inbred lines and to predict hybrid performance and heterosis (Kashiani et al, 2012;Solomon et al, 2012). An important aspect of hybrid and inbred line development is having information about the genetic diversity and the genetic relationship among inbred lines.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of combining ability of sweet corn inbred lines obtained using diallel analysis have been studied considering different agronomic traits, allowing selecting superior hybrid combinations and understanding additive and non-additive genetic effects when determining these traits (Kwiatkowski et al, 2011;Solomon et al, 2012;Rice & Tracy, 2013;Worrajinda et al, 2013).…”
Section: Resumo Dialelo Parcial E O Potencial De Linhagens De Milho Smentioning
confidence: 99%